2014
DOI: 10.1007/s11033-013-2975-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms in the promoter region of interleukin-10 and susceptibility to inflammatory bowel disease

Abstract: The aim of this study was to assess the association of polymorphisms in the promoter region of the IL-10 gene with the risk of inflammatory bowel disease (IBD), including Crohn's disease (CD) and ulcerative colitis (UC). Fifteen studies (3,693 cases and 4,574 controls) were included in a meta-analysis of association between IL-10 -1082G/A, -819C/T and -592C/A polymorphisms, and IBD, CD and UC using allele contrast and the recessive, dominant, and additive models. Hardy-Weinberg equilibrium was confirmed for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…On the other hand, no significant association was found either with alleles or genotypes of -1082 G/A polymorphism and UC in Saudi patients. These results are in accordance with the various reports, which also indicted an association of IL-10-1082G/A polymorphism susceptibility to IBD [89,122]. A meta-analysis including 18 case-control studies provided evidence for the association between IL-10-1082G/ A polymorphism and susceptibility of CD [122].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, no significant association was found either with alleles or genotypes of -1082 G/A polymorphism and UC in Saudi patients. These results are in accordance with the various reports, which also indicted an association of IL-10-1082G/A polymorphism susceptibility to IBD [89,122]. A meta-analysis including 18 case-control studies provided evidence for the association between IL-10-1082G/ A polymorphism and susceptibility of CD [122].…”
Section: Discussionsupporting
confidence: 92%
“…A meta-analysis including 18 case-control studies provided evidence for the association between IL-10-1082G/ A polymorphism and susceptibility of CD [122]. Another met-analysis including 15 studies demonstrated clear association between the IL-10-1082G/A polymorphisms and the risk of IBD [89]. The allele G of -1082G/A polymorphism has been associated with the IBD, and higher serum levels of IL-10 concentration have been reported in IBD patients than in the controls [72,90].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most studies failed to find any association between IL10 promoter SNPs and susceptibility to develop IBD (Klein et al 2000;Koss et al 2000;Kim et al 2003;Balding et al 2004;Cantor et al 2005;Klausz et al 2005;Celik et al 2006;Sanchez et al 2009;Andersen et al 2010;Ahirwar et al 2012;Doecke et al 2013;Bank et al 2014;LopezHernandez et al 2015). Moreover, three meta-analysis, performed so far, were not consistent either, with each one showing associations of some of the three SNPs with one form of IBD that were not replicated by others (Zhu et al 2013;Lv et al 2014;Zou et al 2014). Interestingly, GWAS analyses did not find any evidence of association for those SNPs in IL10 promoter region with UC or CD (Barrett et al 2008;Franke et al 2008).…”
Section: Discussionmentioning
confidence: 88%
“…Functional significance of these polymorphisms have been demonstrated both in vitro (Turner et al 1997;Tagore et al 1999) and in vivo (Ouma et al 2008), associating GCC haplotype with high, ACC with intermediate and ATA haplotype with low IL-10 production. A number of studies in different populations and three meta-analyses have addressed the association of one or more of these SNPs in IL10 promoter region with IBD, but the results were inconsistent (Zhu et al 2013;Lv et al 2014;Zou et al 2014). Thus, the role of these three common IL10 SNPs in IBD susceptibility, although probable, has not been elucidated yet.…”
Section: Introductionmentioning
confidence: 99%